“Él ama la justicia y el derecho”: Aportes sobre ley, derecho y altos tribunales de Justicia en Hispanoámerica (Res Gesta, 2018)
This article attempts to highlight the categories that were built between the Middle Ages and the Modern Era on the law and the right, as well as the centrality that met Audiencias and Chancillerias will of the Castilian monarch in the implementation of Justice as a cardinal virtue of the monarchy of those centuries.
Keywords: Right; Law; Audiencias; Hispanic America